Pelatihan Penggunaan Game Quizizz dalam Meningkatkan Pengetahuan Siswa Tentang Perangkat Komputer - Febby Madonna Yuma; Andy Sapta; Parini Parini (Smart Education, 2022)
Abstract: In this current era, all students are required to be able to maximize the use of technology in learning. With the influence of increasingly widespread gadgets, making students' interest in learning decrease, it is necessary to have an interesting digital learning application so that students of SMP N 1 Pulo Banding are interested in learning about computer devices. The purpose of this training is to increase students' understanding of SMP N 1 Pulo Banding regarding learning technology using the Quizizz game application in increasing students' knowledge of computer devices. Game Quizzes is a game-based educational application for interactive and fun assessments. The training method is carried out in the form of lectures, discussions, and practice. The evaluation of this training was conducted using an open questionnaire to determine the extent of students' knowledge of computer equipment. The evaluation results show that the use of Quizizz games is very interesting and can increase students' learning motivation. The conclusion of the training shows that there is an increase in students' knowledge of SMP N 1 Pulo Banding about computer equipment.Keywords: quizz game; computer hardware; student; technologyAbstrak: Pada era sekarang ini, semua siswa dituntut untuk dapat memaksimalkan penggunaan teknologi dalam pembelajaran. Dengan pengaruh gadget yang semakin marak, membuat minat belajar siswa semakin menurun, sehingga perlu adanya aplikasi pembelajaran digital yang menarik agar siswa SMP N 1 Pulo Bandring tertarik untuk belajar tentang perangkat komputer. Tujuan Pelatihan ini untuk meningkatkan pemahaman siswa SMP N 1 Pulo Bandring mengenai teknologi pembelajaran dengan menggunakan Aplikasi game Quizizz dalam meningkatkan pengetahun siswa tentang perangkat komputer. Game Quizziz merupakan aplikasi pendidikan berbasis game untuk penilaian interaktif dan menyenangkan. Metode pelatihan dilakukan dalam bentuk ceramah, diskusi dan praktek. Evaluasi pelatihan ini dilakukan dengan kuesioner terbuka untuk mengetahui sejauh mana pengetahuan siswa tentang perangkat komputer. Hasil evaluasi menunjukan bahwa penggunaaan game Quizizz sangat menarik dan dapat menigkatkan motivasi belajar mahasiswa. Adapun kesimpulan pelatihan menunjukan bahwa terjadinya peningkatan pengetahuan siswa SMP N 1 Pulo Bandring tentang perangkat komputer. Kata Kunci: game quizizz; perangkat komputer; siswa; teknologi